Pengaruh Norma Subjektif Dan Kontrol Perilaku Yang Dipersepsikan Terhadap Niat Pinjam KUR Mikro ( Studi Pada Nasabah BRI di Pati) - Maskur, Ali; Tjahjaningsih, Endang; Saeroji, Adib (Proceeding Fakultas Ekonomi, 2015)
Abstract: This study aimed to examine the effect of Subjective Norms,Perceived Behavioral control Interest to Loan Products Micro KUR in Pati ( Studies to pati customers ) This study included in the quantitative research using survey method through descriptive analysis approach.This study uses census techniques where the of population is 150 persons prospective customers BRI, while the data is processed as many as 121 candidates nasbah. Measurements using a Likert scale with 5 (five) alternative answers. Test instruments used are validity and reliability. Normality Test (Sample 1-KS) Classical Assumption Test (test heterokedastisitas) The test model used is the coefficient of determination (R2) and the F test (Goodness of Fit). Test this hypothesis using regression analysis.Based on the results of the study can be summarized as follows: (i) subjective norm does not affect the intention, (ii) Perceived Behavioral Control positive and significant effect on the Intention.Keywords: NORMA SUBJECTIVE, PERCEIVED BEHAVIORAL CONTROL, INTENTION LOANS KUR